Evolutionary Changes in the Chromatin Landscape Contribute to Reorganization of a Developmental Gene Network During Rapid Life History Evolution in Sea Urchins. (10th August 2022) - Davidson, Phillip L; Byrne, Maria; Wray, Gregory A
Abstract: Chromatin configuration is highly dynamic during embryonic development in animals, exerting an important point of control in transcriptional regulation. Yet there exists remarkably little information about the role of evolutionary changes in chromatin configuration to the evolution of gene expression and organismal traits. Genome-wide assays of chromatin configuration, coupled with whole-genome alignments, can help address this gap in knowledge in several ways. In this study we present a comparative analysis of regulatory element sequences and accessibility throughout embryogenesis in three sea urchin species with divergent life histories: a lecithotroph Heliocidaris erythrogramma, a closely related planktotroph H. tuberculata, and a distantly related planktotroph Lytechinus variegatus . We identified distinct epigenetic and mutational signatures of evolutionary modifications to the function of putative cis -regulatory elements in H. erythrogramma that have accumulated nonuniformly throughout the genome, suggesting selection, rather than drift, underlies many modifications associated with the derived life history. Specifically, regulatory elements composing the sea urchin developmental gene regulatory network are enriched for signatures of positive selection and accessibility changes which may function to alter binding affinity and access of developmental transcription factors to these sites. Furthermore, regulatory element changes often correlate with divergent expression patterns of genes involved in cell type specification, morphogenesis, and development of other derived traits, suggesting these evolutionary modifications have been consequential for phenotypic evolution in H. erythrogramma . Collectively, our results demonstrate that selective pressures imposed by changes in developmental life history rapidly reshape the cis -regulatory landscape of core developmental genes to generate novel traits and embryonic programs.